Literature review applying therapeutic theory and practice in the field of domestic abuse and coercive control - Smith, Ruth (European Journal for Qualitative Research in Psychotherapy, 2023)
This literature review introduces the issue of domestic abuse and coercive control to psychotherapists and considers how to work therapeutically with survivors. It will provide a definition of domestic abuse and coercive control, including discussion about post-separation abuse and domestic homicide. Drawing on my own experience of working with survivors of domestic abuse and sexual violence as a psychotherapist, combined with the work of notable figures in the field of trauma therapy, I will outline the recommended therapeutic approach to working with survivors. It is hoped this article will contribute to the field of psychotherapy and the call for mental health professionals to be aware of domestic abuse. Finally, this article supports the stance that domestic abuse is a human rights violation and positions psychotherapy with survivors as an act of social justice.